Moraxella catarrhalis induces CEACAM3‐Syk‐CARD9‐dependent activation of human granulocytes. (3rd May 2016) - Heinrich, A.; Heyl, K.A.; Klaile, E.; Müller, M.M.; Klassert, T.E.; Wiessner, A.; Fischer, K.; Schumann, R.R.; Seifert, U.; Riesbeck, K.; Moter, A.; Singer, B.B.; et al.
Summary: The human restricted pathogen Moraxella catarrhalis is an important causal agent for exacerbations in chronic obstructive lung disease in adults. In such patients, increased numbers of granulocytes are present in the airways, which correlate with bacteria‐induced exacerbations and severity of the disease. Our study investigated whether the interaction of M .  catarrhalis with the human granulocyte‐specific carcinoembryonic antigen‐related cell adhesion molecule (CEACAM)‐3 is linked to NF‐ κ B activation, resulting in chemokine production. Granulocytes from healthy donors and NB4 cells were infected with M .  catarrhalis in the presence of different inhibitors, blocking antibodies and siRNA. The supernatants were analysed by enzyme‐linked immunosorbent assay for chemokines. NF‐ κ B activation was determined using a luciferase reporter gene assay and chromatin‐immunoprecipitation. We found evidence that the specific engagement of CEACAM3 by M. catarrhalis ubiquitous surface protein A1 (UspA1) results in the activation of pro‐inflammatory events, such as degranulation of neutrophils, ROS production and chemokine secretion. The interaction of UspA1 with CEACAM3 induced the activation of the NF‐ κ B pathway via Syk and the CARD9 pathway and was dependent on the phosphorylation of the CEACAM3 ITAM‐like motif. These findings suggest that the CEACAM3 signalling in neutrophils is able to specifically modulate airway inflammation caused by infection with M .  catarrhalis .